1944
DOI: 10.1097/00000658-194406000-00009
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomic Study of the Lumbosacral Region in Relation to Low Back Pain and Sciatica

Abstract: FOR MANY YEARS the syndrome of low back pain with associated sciatic nerve radiation has been a subject for investigationi. The complex anatomy of the lumbosacral and sacro-iliac regions, combined with nlumerous anatomic variations, has complicated the problem of etiology of this clinical entity.Two etiologic factors are now generally accepted as the basis for low back pain and sciatica. It has been conclusively shown that pain may arise in the joinits, ligaments and muscles of the lumbosacral region and be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Cadaveric dissections performed by Larmon [10] proved that congenital malformations of S1 can be an independent cause of low back pain and sciatica by compromising the L5 or S1 nerve roots at the intervertebral foramen. He described 2 variants of S1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadaveric dissections performed by Larmon [10] proved that congenital malformations of S1 can be an independent cause of low back pain and sciatica by compromising the L5 or S1 nerve roots at the intervertebral foramen. He described 2 variants of S1.…”
Section: Discussionmentioning
confidence: 99%
“…He described 2 variants of S1. The first characterised by projections emerging from the posterior margin of vertebral body, causing impingement on the nerve root; the second characterised by a deep groove on the limit between the body and the transverse processes of S1, causing sharp bending and entrapment of L5 nerve root due to ligamentous fibres [10].…”
Section: Discussionmentioning
confidence: 99%
“…The earlier observations published [3,8,11,12,13] indicated that the ligaments occur in a random pattern and were distributed arbitrarily in nonsymmetrical patterns. In this study, the authors claimed that these ligaments were not anomalous and were probably developmental in origin.…”
Section: Discussionmentioning
confidence: 99%
“…The osteometric assessment of the intervertebral foramen is just an approximate estimation of its in vivo size, which depends on soft-tissue and dynamic components (Bose and Balasubramaniam, 1984;Cinotti et al, 2002;Crock, 1981;Epstein et al, 1962;Fujiwara et al, 2001;Hoyland et al, 1989;Larmon, 1944;Lee et al, 1988;Lu et al, 2000;Magnuson, 1944;Mayoux-Benhamou et al, 1989;Stephens et al, 1991;Swanberg, 1915;Vital et al, 1983;Yoo et al, 1992;Yoshida et al, 1992). The lack of any soft tissue (which for this region includes nerves, lymphatic vessels, venous plexus, and arteries) could not be overcome in our study.…”
Section: Clinical Importancementioning
confidence: 99%